2015
DOI: 10.1038/srep15685
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Hepatobiliary Excretion of Micelle-Encapsulated/Radiolabeled Upconverting Nanoparticles as an Integrated Form

Abstract: In the field of nanomedicine, long term accumulation of nanoparticles (NPs) in the mononuclear phagocyte system (MPS) such as liver is the major hurdle in clinical translation. On the other hand, NPs could be excreted via hepatobiliary excretion pathway without overt tissue toxicity. Therefore, it is critical to develop NPs that show favorable excretion property. Herein, we demonstrated that micelle encapsulated 64Cu-labeled upconverting nanoparticles (micelle encapsulated 64Cu-NOTA-UCNPs) showed substantial h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Recently, Seo et al reported the synthesis of micelle encapsulated up-conversion nanoparticles conjugated with NOTA chelator for 64 Cu labeling. 103 The radiolabeled up-conversion nanoparticles were administered in normal mice. In vivo PET imaging and up-conversion luminescence imaging showed the nanoparticles cleared from the biological system primarily through hepatobiliary excretion, which was further verified by TEM investigation.…”
Section: Preclinical Studies With Radiolabeled Inorganic Nanoparticlesmentioning
confidence: 99%
“…Recently, Seo et al reported the synthesis of micelle encapsulated up-conversion nanoparticles conjugated with NOTA chelator for 64 Cu labeling. 103 The radiolabeled up-conversion nanoparticles were administered in normal mice. In vivo PET imaging and up-conversion luminescence imaging showed the nanoparticles cleared from the biological system primarily through hepatobiliary excretion, which was further verified by TEM investigation.…”
Section: Preclinical Studies With Radiolabeled Inorganic Nanoparticlesmentioning
confidence: 99%
“…The excretion of multiple metabolites of engineered nanoparticles should take place via both routes, however, nanoparticle excretion is varied between phagocytosis, hepatobiliary and/or renal excretion according the characteristics of each radiolabeled nanoparticle. In an example of a radiolabeled upconversion nanoparticle (UCNP), radiolabeled UCNPs gathered in hepatic vascular sinusoids, were taken up by hepatocytes and finally excreted via bile canaliculi in their integral form rather than been taken up in Kupffer cells (83). This study of the excretion pathway using radioactivity and upconversion-luminescence imaging using 64 Cu-labeled UCNP confirmed the excretion in the integral Systemically administered nanoparticles encounter various biological molecules and several reactions take place.…”
Section: Issues Of In Vivo Behavior Investigated By Radionanomedicinementioning
confidence: 79%
“…This was different from excretion of another radiolabeled nanoparticle after the capsular detachment from the nanoparticles (83). As a different excretion pathway, direct excretion from intestines mediated by goblet cells was also reported, not mediated by hepatobiliary excretion (84).…”
Section: Issues Of In Vivo Behavior Investigated By Radionanomedicinementioning
confidence: 99%
“…[138] In a more recent study, bimodal in vivo imaging was employed to demonstrate hepatobiliary excretion of micelle-encapsulated UCNPs via PET and upconversion luminescence imaging. [139] 64 Cu-NOTA-UCNPs displayed high radiochemical purity (~99%) and reasonable serum stability (100 % upto 4 h and ~75% after 24 h). The multiplexing capabilities of UCNPs were very ably demonstrated in a recent exciting study by Rieffel et.al who reported a hexamodal porphyrin-phospholipid-coated UCNP (PoP-UCNP) system, where the exquisite affinity of copper for porphyrins was used for post-labeling of UCNPs with 64 Cu by simple incubation (>80% labeling yield).…”
Section: Radiolabeled Nanomaterials For Cancer Theranosticsmentioning
confidence: 99%